2017
DOI: 10.1080/13548506.2017.1327667
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among healthcare workers at L’Aquila: its prevalence and associated factors

Abstract: Burnout, which is now recognized as a real problem in terms of its negative outcome on healthcare efficiency, is a stress condition that can be increased by exposure to natural disasters, such as the 2009 L'Aquila earthquake. This study aims to evaluate burnout syndrome, its associated risk factors and stress levels, and the individual coping strategies among healthcare professionals at L'Aquila General Hospital. A cross-sectional study of 190 healthcare workers was conducted. There was a questionnaire for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…Generally, our findings, even if limited by this small-scale protocol, seemed to confirm the positive psychotherapy role after BC diagnosis and treatment through the impact of the cognitive processes, coping strategies, and psychological resilience (Kolokotroni et al, 2014; Parikh et al, 2015; Di Giacomo et al, 2015, 2016; Koutrouli et al, 2016; Mattei et al, 2017a,b). In fact, they are considered key factors in personal change, in dealing positively with, and overcoming, the cancer experience.…”
Section: Resultssupporting
confidence: 64%
“…Generally, our findings, even if limited by this small-scale protocol, seemed to confirm the positive psychotherapy role after BC diagnosis and treatment through the impact of the cognitive processes, coping strategies, and psychological resilience (Kolokotroni et al, 2014; Parikh et al, 2015; Di Giacomo et al, 2015, 2016; Koutrouli et al, 2016; Mattei et al, 2017a,b). In fact, they are considered key factors in personal change, in dealing positively with, and overcoming, the cancer experience.…”
Section: Resultssupporting
confidence: 64%
“…This study found a high rate of non-specific psychiatric morbidity in trauma-exposed New Zealand paramedics. This is at the upper end of those previously reported in health professional groups, yet consistent with studies where this is assessed as part of wider enquiries about wellbeing and recovery from critical events (10,45). These symptoms are not benign, with their known association with burnout and job stress.…”
Section: Discussionsupporting
confidence: 86%
“…Being consistent with Herbert Freuden berger 1974 describing it as a sense of failure and an exhausting experience resulting from an overload of energy requirements, which not far from reality found in this study, which particularly affected the healthcare area showed this circumstances in their performance, claiming feel sometimes with a high degree of frustration and fatigue. 18 Linking it quoted at the time by Pines et al, 19 who indicate that burnout is an affectation without exclusivity for health professionals and confidence to, the damage that triggers this syndrome also affects administrative and support workers organizations as well could demonstrated in the relationship of the results with workers tested, it also stated categorically by the principles of Castaneda et al 21 where it is stated that the interaction with users of medical services can generate more problems related to the syndrome. Contrary to the assertions of Adriana Arce et al, 22 who indicated in his study in the hospital current noting that burnout is present and a high incidence of physicians in public hospitals find more involvement nurses and nursing assistants.…”
Section: Discussionmentioning
confidence: 88%
“…17 When implemented will allow timely care in occupational hygiene and prevent diseases and disabilities that may affect occupational health of employees. 18 Pines and aorson propose a broader definition, not restricted to professionals help: "It's the mental, physical and emotional exhaustion, caused by chronic involvement in work situations with emotional demands, 19 excessive psychological demands not only give direct service to public, but may also occur in other fields work, and management positions in commercial work, politics etc. It stresses the importance, from preventing the quality of interpersonal relationships at work, supervision and mode of continuous learning opportunities and career development with which count the worker.…”
Section: Introductionmentioning
confidence: 99%